2006
DOI: 10.2139/ssrn.924565
|View full text |Cite
|
Sign up to set email alerts
|

Can Hedge-Fund Returns Be Replicated?: The Linear Case

Abstract: Hedge funds are often cited as attractive investments because of their diversification benefits and distinctive risk profiles-in contrast to traditional investments such as stocks and bonds, hedge-fund returns have more complex risk exposures that yield complementary sources of risk premia. This raises the possibility of creating passive replicating portfolios or "clones" using liquid exchange-traded instruments that provide similar risk exposures at lower cost and with greater transparency. Using monthly retu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
179
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(188 citation statements)
references
References 41 publications
8
179
0
1
Order By: Relevance
“…Factor-based risk-adjusted returns have also been applied by Fung and Hsieh [2004] for benchmarking hedge fund performance. Hasanhodzic and Lo [2007] extended this approach to replicating North American hedge fund returns, while Hakamada, Takahashi, and Yamamoto [2007] applied it to analyze Asian hedge fund returns.…”
Section: Overall Risk and Return Characteristics Of North American Anmentioning
confidence: 99%
“…Factor-based risk-adjusted returns have also been applied by Fung and Hsieh [2004] for benchmarking hedge fund performance. Hasanhodzic and Lo [2007] extended this approach to replicating North American hedge fund returns, while Hakamada, Takahashi, and Yamamoto [2007] applied it to analyze Asian hedge fund returns.…”
Section: Overall Risk and Return Characteristics Of North American Anmentioning
confidence: 99%
“…As with Jaeger and Wagner (2005), Hasanhodzic and Lo (2007), and Amenc et al (2010), we assess the out-of-sample replication quality of the Eta model by attempting to clone the time-series characteristics of HMFs.…”
Section: Replicationmentioning
confidence: 99%
“…As fund managers adopt different trading strategies, ABS factors are identified that align themselves to these strategies ( Jaeger and Wagner, 2005), in contrast to the same set of factors for all strategies (Hasanhodzic and Lo, 2007). Sharpe (1992) introduced these style factor models to active equity mutual funds, which were subsequently extended by Fung and Hsieh (1997) to hedge funds.…”
Section: Performance Evaluation Of Hmfsmentioning
confidence: 99%
“…A further advantage of this methodology is that if the linear model is wellspecified, one can attempt to replicate the returns of the hedge fund by investing in the appropriate portfolio of factors. A recent paper by Hasanhodzic and Lo (2007) provides some evidence that linear replication can be successful for certain strategies whilst offering certain advantages to hedge fund investing. These include more transparency, increased liquidity and fewer capacity constraints.…”
Section: Introductionmentioning
confidence: 99%